Paradigma Baru lslam di Indonesia - Ali-Fauzi, Ihsan (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1997)
This book is product of a series of conferences designed for serious scholars who wish to investigate new trends of Islamic thought in Indonesia. It is intended to meet e need felt by those whose understanding of Indonesian Islam has been hampered by a number of major developments of religious phenomena since the advance of the New Order regime that, to a significant degree, provides a new paradigm among Indonesian Muslims. the purpose of this book, according to the editor, is to provide an academic map through political and anthropological studies; it seeks to present Muslim's perspective in the light